Rank Intersectionality and Othello - Innes, Paul (Multicultural Shakespeare: Translation, Appropriation and Performance, 2024)
As a crucial concept in critical theory, intersectionality satisfies a need within global Shakespeare reception studies. The reason for this is the way it permits cross-currents between conceptions of race and gender in particular; it also allows for an awareness of the historical and cultural location of the audience or reader as distinct from the moment of the production of a particular play. It is therefore fundamentally dynamic and can be further extended via discussions of rank, sexuality or religion. This essay argues for the importance of a lively approach to intersectionality that integrates concerns of race and gender in Othello with social rank in Shakespearean Venice and Cyprus. The article deliberately eschews a psychological analysis of character, insisting that a sense of inwardness, that these stage figures should somehow be treated as though they were real people, is a much later, modern preoccupation. Instead, the play is treated as not only early modern but pre-modern. This is also why there is no treatment of class as such; that too is a much later modern category that carries all sorts of baggage, anachronistic and otherwise. Class is not a sophisticated enough notion to account adequately for the permutations in a society that was obsessed with tiny gradations in rank, dignity and honour. Beginning with reference to Toni Morrison’s conceptualization of modern American literature as predicated on a constructed whiteness, the essay moves by analogy back towards Shakespeare’s drama to the structured interplay between gender, rank and race that is this play. Althusser’s sense of interpellation is revived in order adequately to describe how these positions work to emplace Othello and Desdemona in order to open up the play to a global perspective that accounts for multiple possibilities. The article therefore goes well beyond the old familiar groupings so beloved of character-based criticism, instead insisting on the primacy of social definitions of the positions available to the personages in the play.